Analisis Kinerja Keuangan PT Bank Central Asia TBK Periode 2020–2024 Berdasarkan Rasio Keuangan Perbankan - Andy Garcia Ridwan; Rasmita Dinata; Sri Retnaning Sampurnaningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the financial performance of PT Bank Central Asia Tbk (BBCA) during the 2020–2024 period using a financial ratio analysis approach, covering asset quality, liquidity, profitability, operational efficiency, and solvency. The research employs a descriptive quantitative method with ratio analysis techniques based on the company’s annual financial statements. The results indicate that PT Bank Central Asia Tbk demonstrates strong financial performance throughout the study period. Asset quality remains well maintained, as reflected by an average Non-Performing Loan (NPL) ratio of 2.02%. Liquidity conditions are robust, evidenced by an average Loan to Deposit Ratio (LDR) of 69.56% and a Liquidity Coverage Ratio (LCR) consistently exceeding the minimum regulatory requirements. In terms of profitability, Return on Assets (ROA) and Return on Equity (ROE) show favorable performance with an upward trend. Furthermore, a low BOPO ratio indicates high operational efficiency, while a Capital Adequacy Ratio (CAR) well above regulatory standards reflects strong capital resilience. Overall, the findings suggest that PT Bank Central Asia Tbk was in a sound financial condition during the 2020–2024 period.